POLITIK HUKUM PENGUASAAN TANAH BERDASARKAN KETETAPAN MPR TENTANG PEMBARUAN AGRARIA DAN PENGELOLAAN SUMBER DAYA ALAM - Gunawan, Ade (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
Agrarian reform is a continuous process regarding the rearrangement of control, ownership, use, and utilization of agrarian resources carried out in the context of achieving legal certainty and protection as well as justice and prosperity for all the people of Indonesia. the purpose of this research is first to find out the current politics of land law and the second goal is to find out the direction of development and renewal of national land law towards structuring control and ownership of land. The method of approach in this research is the statutory approach method (statute approach). The politics of land law towards the structuring of land control and ownership in the reform era was issued by the People's Consultative Assembly Decree No. IX/MPR/2001 on Agrarian Reform and Natural Resource Management in order to overcome inequality in land control and ownership for the benefit of the community. Then the direction of development and reform of national land law towards the structuring of land tenure and ownership is to ensure the realization of equitable tenure and ownership of land for all people based on TAP MPR Number IX/MPR/2001 on Agrarian Reform and Natural Resource Management the demands of the reform era.